An ultra-low-power highly integrated novel one-cell battery management chip for wearables. (December 2022) - Wu, Kai-Kai; Wang, Hong-Yi; Chen, Chen; Tao, Tao
Abstract: In this study, a new battery management chip is presented. By integrating discrete charging and discharging field effect transistors (FETs) into the battery management chip, there are adjusted to a single switch by switching the substrate of this internal switch. A new current detection method is designed to replace the external resistance sensor, which reduces the space overhead and cost of the battery management system. Compared with the conventional battery management chip, the proposed chip significantly improves the application density. Based on the 0.18 μm 5 V process, the circuit and switch were integrated into a one-cell battery management chip. Furthermore, the fabricated chip module demonstrates the effectiveness of the introduced architecture in reducing space for wearable applications.